Economic status of agriculture labour: A case study of Rajasthan (IASH Indian Journal of Arid Horticulture, 2026)
The study was conducted to examine the socio-economic status of agricultural labours, analyze wage and employment patterns, assess income and expenditure patterns, and investigate gender discrimination among agricultural labour in Rajasthan. The collected data revealed that the socio-economic status of agricultural labour was below the average compared to workers in other sectors. The highest level of employment was generated through crop harvesting activities. Annual employment in agriculture averaged 214 days. The average wage rate was ₹ 332.64 in the agricultural sector and ₹ 406.73 in the non-agricultural sector. The total annual family income and total family expenditure were ₹ 194,957 and ₹ 157,857, respectively.